Non-Saccharomyces Killer Toxins: Possible Biocontrol Agents Against Brettanomyces in Wine? - Mehlomakulu, N.N.; Setati, M.E.; Divol, B. (South African Journal of Enology and Viticulture, 2016)
Red wine spoiled by the yeast Brettanomyces bruxellensis is characterised by off-odours commonly described as horse sweat, phenolic, varnish and band-aid. The growth of this yeast in wine is traditionally controlled by the use of sulphur dioxide (SO2). However, the concentration of SO2, the pH of the wine, the presence of SO2-binding chemical compounds in the wine, as well as the strain of B. bruxellensis, determine the effectiveness of SO2. Other chemical preservatives have been tested, but are not much more efficient than SO2, and methods used to clean barrels are only partially effective. Filtration of wine and the use of electric currents/fields are also reported to alter the physical and sensory properties of wine. In this context, alternative methods are currently sought to achieve full control of this yeast in wine. Killer toxins have recently been proposed to fulfil this purpose. They are antimicrobial compounds secreted by Saccharomyces and non-Saccharomyces yeasts, displaying killer activity against other yeasts and filamentous fungi. They are believed to play a role in yeast population dynamics, and this killer phenotype potentially could be exploited to inhibit the growth of undesired microorganisms within a microbial ecosystem such as that occurring in wine. In this review, non-Saccharomyces killer toxins are described and their potential application in inhibiting B. bruxellensis in wine is discussed in comparison to other tried methods and techniques.